Pengaruh Kualitas Produk, Kualitas Pelayanan dan Citra Perusahaan terhadap Keputusan Nasabah dalam Menabung: Studi Kasus Bank Muamalat Kantor Cabang Medan Balai Kota - Syarifah, Nuraisyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the influence of product quality, service quality and company image on savings decisions. The variables used are product quality (X1), service quality (X2) and company image (X3) on saving decisions (Y). The type of research used is quantitative research using surveys and distributing questionnaires. The sampling technique used was a non-probability sampling method with a total of 80 respondents. The analytical method used in this research is multiple linear regression. Research data processing was carried out using the Statistical Package for the Social Sciences version 20 (SPSS) tools. The research results showed that simultaneously the variables product quality, service quality and company image had a positive effect on purchasing decisions at the Bank Muamalat Medan City Hall Branch Office. 79% of product quality, service quality, company reputation and profit sharing can influence customer decision variables in saving while the remaining 21% of customers' decisions to take financing are influenced by other variables not examined in this research. Keywords: product quality, service quality, company image, saving decisions.